The design of mechanical systems in residential villa tira – Ram Allah - Naser, Hussain; Hamdan, Ezat (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2007)
This project comes as the fruit of five years of hard work in the field of refrigeration and air conditioning engineering . in this study ageneral study will be ......
no of pages 77 , 23667 , ميكانيك 142007 , in the store
Keywords: mechanical systems; residential villa tira